STRATEGI SUPLEMENTASI LEGUMINOSA UNTUK MENINGKATKAN PENAMPILAN DOMBA - Eko Marhaeniyanto; Sri Susanti (BUANA SAINS, 2011)
Research using potential local leguminosa to used supplementation with basal diet rice straw to effort effects on intake, nutrient digestibility and daily gain sheep. Research materials consisted of 16 rams, average body weight 13,10 ± 0,4 kg, placed in 16 individual cages. Treatment of feed used are rice straw, Gliricidia maculata and Leucaena leucocephala. Research methods in vivo experiments with randomized block design (RBD), which consists of 4 treatments and 4 replications. The treatment consisted of level legume supplementation on R0 (0%), R1 (0.25%), R2 (0.5%), and R3 (1.0%). The results legume supplementation on basal diet of rice straw showed very significant on feed intake, digestibility and intake digested of feed (P0.05). Conclution in this research: supplemented legume Gliricidia maculata and Leucaena leucocephala 1.0% BW on basal diet rice straw shows feed intake, digestibility and daily gain tend to give better performance